MEMPERSIAPKAN IBU HAMIL YANG SEHAT MELALUI KELAS IBU HAMIL PADA MASA PANDEMI COVID 19 DENGAN MENGGUNAKAN SMARTPHONE DI WILAYAH KERJA PUSKESMAS SIDOMULYO RAWAT INAP KOTA PEKANBARU - YAN SARTIKA,; ELLY SUSILAWATI, (KRIDA CENDEKIA, 2021)
The purpose of this community service activity is to increase knowledge, change attitudes and behavior of pregnant women in realizing a Healthy Generation during the Covid 19 Pandemic in Mother's class by using smartphones. This method of community service activity is carried out by conducting outreach to pregnant women about taking classes for pregnant women via Smartphones so that pregnant women stay healthy during the Covid 19 Pandemic. The material is delivered by viewing educational blogs about classes for pregnant women which are accessed via Smartphones. The result of this community service activity is that there have been 4 meetings for pregnant women during the COVID-19 pandemic, 4 meetings at the Sidomulyo Health Center, Pekanbaru City. Based on the results of monitoring and evaluation at the 1st meeting, 80% of participants were well informed and 20% had sufficient knowledge, at the 2nd meeting 86.67% of the participants had good knowledge and 13.33% had sufficient knowledge, at the 3rd meeting 73.33% of the participants had good knowledge and 26.67% had sufficient knowledge, at meeting 4, 80% of participants had good knowledge and 20% had sufficient knowledge. It is recommended for pregnant women to be more active in seeking information about knowledge in pregnant women's classes through books and social media so that they can increase knowledge of pregnant women and can produce a superior generation.